Gifted Rural Learners: Exploring Power, Place, and Privilege with a Focus on Promising Practices: An Introduction to Volume 10, Issue 2 of TPRE - Novak, Angela M. (Theory & Practice in Rural Education, 2020)
This special issue of Theory & Practice in Rural Education highlights gifted rural learners; the call sought papers on the concepts of power, place, privilege, or promising practices in the field of gifted rurality. This introductory article provides a brief synopsis of each of the seven peer reviewed articles and an analysis of three principal themes that emerged from the articles: equity, identity, and a sense of place. Additionally, three questions regarding gifted rurality are explored: How does gifted education view equity in the context of rurality? How does intersectionality impact gifted students? How does (or should) gifted education as a field adjust in order to recognize the strengths and assets of our gifted rural students?